Analisis Beberapa Faktor Yang Mempengaruhi Produktivitas Dan Pendapatan Peternak Babi Di Kecamatan Kubutambahan Kabupaten Buleleng - Putu Sabda Yasa; I Gusti Wayan Murjana Yasa (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2022)
In addition to being large in number, the Indonesian workforce also has a low average level of education. This phenomenon makes it difficult for the majority of the Indonesian workforce to work in the formal sector, provided that they have a high level of education and expertise. One alternative to overcome the above problems is by empowering the agricultural sector, one of which is the livestock sector. One of the potential farms to be developed in Bali is pig farming, where pig farming in Bali has played a very important role in supporting the people's economy, especially in rural areas. This study aims to determine the variables of working capital, labor, work experience, and productivity on income and the productivity variables mediate the effect of working capital, labor, and work experience on the income of pig farmers in Kubutambahan District. This study uses a quantitative method in the form of associative. The research locations are in Evidence Village, Kubudindingan Village, Bengkala Village, Bila Village, Tamblang Village, Bulian Village, Tunjung Village, Mengening Village, and Tajun Village, which are in the Kubudindingan District. The data obtained was tested using the method of path analysis or (path analysis) of the data obtained through questionnaires, interviews and observations. The results of the study stated that working capital, labor, and work experience had a significant positive effect on the productivity of pig farmers. Working capital, labor, work experience, and productivity have a significant positive effect on the income of pig farmers. Productivity is able to mediate the effect of working capital, labor, and work experience on the income of pig farmers in Kubudinding District, Buleleng Regency.